Analysis of Fixed Asset Management Case Study of North Sumatra DPRD - Alyaa Zafira Darmawan; Hendra Harmain (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Fixed assets or assets are all goods purchased and obtained at the expense of the State Revenue and Expenditure Budget (APBN) or from other legitimate acquisitions, both ongoing and non-running and their parts. This research aims to examine the fixed asset management system based on PSAK No. 7 regarding fixed assets. The purpose of this study was to determine the suitability of the management of fixed assets at the North Sumatra DPRD Office with PSAP No 7. This study also used a qualitative approach, data collection techniques were carried out by interviews and documentation. From the results of research conducted on the management of fixed assets at the North Sumatra DPRD Office, especially in the accounting field regarding recognition, measurement, disclosure, it is in accordance with Government Accounting Standard Statement Number 7.